Implementation of Project-Based Learning Through Merdeka Curriculum in Teaching Speaking Skills - Wahdatul, Siti Wahdatul Alawiah; Rika Perdana, Purnama (Universitas Terbuka, 2025)
This research aims to explore the implementation of Project-Based Learning (PBL) in the Merdeka Curriculum and its impact on students' speaking skills. Using a qualitative approach, this study involves observation, interviews, and document analysis to collect data from eighth-grade students at SMP Maulana Yusuf. The results indicate that PBL significantly improves students' speaking abilities while promoting essential 21st-century skills like teamwork, creativity, and problem-solving. PBL encourages an interactive and engaging learning environment, motivating students to participate and share their ideas confidently and actively. Challenges such as varying students' speaking proficiency levels highlight the need for adaptive teaching strategies to ensure inclusivity. Educators should address diverse learning needs by employing differentiated instruction and providing additional support to students with lower proficiency levels. This research underscores the significant role of PBL in creating a student-centered learning environment that aligns with the goals of the Merdeka Curriculum, which prioritizes independent and active learning. To maximize the benefits of PBL, it is recommended that educators engage in ongoing professional development, design contextually appropriate projects, and foster collaboration with colleagues to refine teaching methods, overcome challenges, and harness PBL's full potential to enhance language skills and support students' comprehensive development.